Despers May Miss Panorama - Unknown (Steelband Supplement)
West Indian Tobacco Gay Desperadoes Steel Orchestra is back home after a successful tour of Zambia, where they played for the President, Dr. Kenneth Kuanda at State House. On the way from Zambia the band stopped over in New York to fulfill engagements. With the band return scheduled on January 30, Panorama may be out for Despers this year.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Concert tours -- Trinidad and Tobago